Participatory Design for Accessible Evacuation Centre for Flood Victims in Kelantan - Wan Mohamad Amin Bin W Seman; Asiah Abdul Rahim; Izawati Tukiman (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2021)
Malaysia has been experienced with many natural disasters such as flood, landslide, earthquake and drought, which resulted in damaging the properties and causing casualties especially during the biggest flooding affected over 36,128 families was in 2014 at East Coast of Malaysia mainly in Kelantan. Public buildings such as schools, religious buildings, including mosques or community halls, have been used as evacuation centres in Malaysia every year. Many studies identified many evacuees were facing many problems, particularly in terms of physical facilities, such as providing improper assistance in terms of facilities, privacy, and many others. This paper objectives are firstly, to review the requirements of the physical facilities for evacuation centre, secondly to assess the components of the physical facilities for evacuation centre and finally to propose the criteria of physical facilities for evacuation centre. A qualitative approach was adopted, and data were collected through observation, interview and secondary data through literature analysis. Three case studies in Kelantan were chosen based on three categories which are small capacity (Veteriner office, Kuala Krai), medium-capacity (Sekolah Menengah Kebangsaan Keroh, Kuala Krai) and big capacity (Sekolah Menengah Kebangsaan Agama Lati, Pasir Mas). The data were analysed to assess the physical facilities provided in the evacuation centre to facilitate the flood victims. The benefit of this research is to give awareness to flood victim for future disaster through technology, management, physical and mental. Thus, evacuation centre is important to create comfortable, privacy and rehabilitated environment to serve the flood victims physically and mentally.